Pengembangan Kesenian Wayang Golek Virtual Berbasis Komputer Dengan Software Opensource - DEW, ossy; Zaini, T M (Jurnal Informatika, 2010)
Human mind changes and modern  life   influnce  traditional art, especially Wayang of Indonesia has begun to rarely performed. Therefore, with the technology and computer resources that can be used to show the art puppet show in this study conducted a virtual puppet design application that uses Augmented Reality. The application is executed using a virtual puppet of digital cameras real-time, also using markers and a computer. Through the camera, a virtual puppet application will identify a marker and then do the loading 3D objects shaped puppet that can allow a user to interact with virtual puppet. User  act as a puppeteer who will deliver in accordance with the puppet show puppet show story and also to load the supporting applications to play gamelan and sinden sound like the real puppet show. The method used is waterfall method. And implemented using C programming language, library ARToolkit, Blender, and Lazarus-based opensource. The application has been tested and the results obtained through questionnaires that this application can motivate users to learn the art puppet using this application. Keyword : wayang, virtual, augmented reality, opensource